2010
DOI: 10.3390/d2040561
|View full text |Cite
|
Sign up to set email alerts
|

The Canarian Camel: A Traditional Dromedary Population

Abstract: The domestic camel (dromedary) is the most important livestock species in the Canary Islands and the most important autochthonous European camel population. After six centuries of a successful adaptation process to the particular environment of the Canary Islands, the abandonment of traditional agriculture has led this population to a major bottleneck. Along with a lack of foreign genetic interchanges, this could lead the population to the brink of extinction. Genetic analysis using 13 microsatellites showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 11 publications
(9 reference statements)
2
19
0
2
Order By: Relevance
“…Camels were first introduced to the Canary Islands beginning with the fifteenth century by the Castilian conquerors; during the course of the following centuries, camels adapted to the islands' climate and were used by local peasants, particularly of Lanzarote and Fuerteventura, to power agricultural implements (e.g. ploughs, watermills), as a riding and pack animal, and for wheeled transport (Morera 1991;Schulz et al 2010). Piebald camels were further imported to the Canary Islands from Western Sahara (possibly from individuals originally belonging to the Oulad Tidrarin, as this tribe was customarily living along the coast of Western Sahara adjacent to the Canary Islands, with which it had historical commercial contacts).…”
Section: Geography Of Piebald Camelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Camels were first introduced to the Canary Islands beginning with the fifteenth century by the Castilian conquerors; during the course of the following centuries, camels adapted to the islands' climate and were used by local peasants, particularly of Lanzarote and Fuerteventura, to power agricultural implements (e.g. ploughs, watermills), as a riding and pack animal, and for wheeled transport (Morera 1991;Schulz et al 2010). Piebald camels were further imported to the Canary Islands from Western Sahara (possibly from individuals originally belonging to the Oulad Tidrarin, as this tribe was customarily living along the coast of Western Sahara adjacent to the Canary Islands, with which it had historical commercial contacts).…”
Section: Geography Of Piebald Camelsmentioning
confidence: 99%
“…Piebald camels were further imported to the Canary Islands from Western Sahara (possibly from individuals originally belonging to the Oulad Tidrarin, as this tribe was customarily living along the coast of Western Sahara adjacent to the Canary Islands, with which it had historical commercial contacts). Indeed, a recent study has shown a clear genetic proximity between camel populations from the Canary Islands and from western Africa (Schulz et al 2010), and Canary Islands' piebald camels are reported as closely related to the piebald 'Western Sahara' breed (Dioli 2013), from which they likely originated. But when this happened is uncertain.…”
Section: Geography Of Piebald Camelsmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est dire la grande confusion qui règne dans la nomenclature et l'identification des races de dromadaire. En dépit des progrès de la biologie moléculaire pour spécifier les filiations et identifier les indicateurs génétiques pertinents, la génétique cameline est balbutiante (Schultz et al, 2010).…”
Section: Pollution Génétique Et Conservation Des Races Localesunclassified
“…They are invaluable genetic tools for animal breeding and quantitative trait locus (QTL) analysis (7,8). The SSR marker system has been widely used for camel genetic diversity (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%